Exploring the role of artificial intelligence in education: a comprehensive perspective - Silva, Altieres de Oliveira; Janes, Diego dos Santos (Review of Artificial Intelligence in Education, 2020)
Objective: This synthesis explores the role of Artificial Intelligence (AI) in augmenting the educational process, addressing the global teacher shortage, and personalizing learning experiences. The objective is to reconcile the potential of AI in revolutionizing education with the pedagogical and ethical nuances highlighted by leading experts. Method: A qualitative analysis of insights from UNESCO MGIEP’s ’Artificial Intelligence for Education’ publication was undertaken. The method involved critically reviewing perspectives on AI’s role in education, its ethical considerations, and the historical evolution of AI systems. Results: The analysis revealed a dual view where AI is positioned as a significant tool for personalizing education and addressing educational disparities. However, it is not seen as altering the fundamental human-centric process of learning but rather augmenting and supporting it. Conclusions: The convergence of perspectives suggests that while AI can greatly enhance the personalization and accessibility of education, it serves best as a complement to human teaching rather than a replacement. The pedagogical integration of AI necessitates a balanced approach that values ethical considerations and the innate complexity of the learning process.